Dampak Psikologis Dan Sosiologis Terhadap Pernikahan Berbeda Setatus Kewarganegaraan - Rohma Nafi Elisa (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
The purpose of this research study is to find out the psychological and social impact on marriage of different citizenship status, in terms of the individualism it feels. The method used to see the psychological and sociological impact on marriage with different citizenship status is by using a literature study research method. This literature study (library research) was taken from several journals, books, and news related to issues of marriage between different countries, from a legal, religious, social, psychological perspective and the relationship between the two. The results of this study can be concluded that, the psychological impact that occurs from both partners, namely: (1) Difficulty in achieving goals in marriage, goals in marriages of different nationalities are like clothes that are used during life. Spirits, beliefs and habits that become rules continue to be added to each person who obeys both in his beliefs and society, including in household life. (2) Maintaining two large families from different countries, all risks must be accepted in marriages of different nationality status because everything is a choice made in finding a partner he chooses in marriage. (3) Fighting for influence in decision-making, both partners usually have a role and impact for their children to follow, especially habits in behavior and religion that they believe in. Then the sociological impacts can be concluded, (1) Communication that has not been fully maximized from the two partners, each individual with other individuals must communicate which is the main tool for fellow individuals to know each other and work together as well as make physical and non-physical contact directly or indirectly direct. (2) The socio-cultural differences held between the two partners, family life in different countries are described as examples of the activities of individual persons as part of which will continue to change at any time. Keywords: Inter-Country Marriage, Psychological, Sociological